Pengaruh Return dan Volume Crypto Currency Pada Bursa Efek Indonesia, Filipina dan Thailand Periode 2020-2022 - Vivin Hanita; Hendra Hendra; Tri Angreni (Komunitas Dosen Indonesia, 2023)
Currently the crypto currency market continues to surge, and is experiencing explosive growth. These fast-rising crypto currencies are attracting the attention of investors and traders, as they offer the potential for huge profits quickly. This study aims to analyze the effect of Crypto currency Return and Volume on Stock Exchanges in 3 Countries, namely Indonesia, Thailand and the Philippines. This analysis uses the time series data regression method. The research period uses a monthly scale from 1 January 2020 to 31 December 2022, with a total of 108 data. The test results show data that crypto currency returns and crypto currency volume have an effect on the movement of the Stock Price Index in Indonesia, Thailand and the Philippines